Prevalence and epidemiological profile of anemia in selected adult workers in Oujda, Morocco - Ouahbi Nawal; Benneser Alaoui Habiba; Serraj Andaloussi Khalid (E3S Web of Conferences)
Anemia is a significant public health problem that may be associated with increased mortality and morbidity. Although the prevalence of anemia has been widely studied in women and children, more studies are needed on adults, including both sexes. This study assessed the prevalence of anemia and its associated factors in a group of adult workers. In July 2024, we conducted a cross-sectional study among Oujda-Angad airport staff. A complete blood count (CBC) diagnosed anemia based on hemoglobin level. The definition and severity of anemia were classified in accordance with the standards defined by the World Health Organization (WHO). Participants' characteristics and nutritional profiles were assessed through a questionnaire-based survey. Data analysis was carried out using SPSS, version 21. We used descriptive analyses and Fisher's Exact test to identify anemia-associated factors. A total of 96 staff were included in the study. The results show that the overall prevalence of anemia was 7.29% in the present study. A higher prevalence of anemia was observed in women (24%) than in men (1.4%). Gender was significantly associated with anemia (p = 0.001). Mild anemia is the predominant form (86%), followed by a single case of moderate anemia. All cases of anemia were symptomatic and without medical history. Except for gender, no significant association between the socioeconomic variables and dietary habits studied and anemia was demonstrated. The nutritional profile of the participants reflects a diverse diet, and most consume iron-rich foods. Our study shows a significant prevalence of anemia in women despite the adoption of a diversified diet. Occupational medicine can conduct systematic screening actions for anemia in workplaces. The findings of this study highlight the importance of exploring the underlying causes of anemia, in order to avoid reducing its causes to nutritional deficiency, especially iron deficiency.